'Bacillus massiliglaciei', a new bacterial species isolated from Siberian permafrost. (January 2017) - Afouda, P.; Dubourg, G.; Cadoret, F.; Fournier, P.-E.; Raoult, D.
Abstract: We describe here the main characteristics of a new species isolated from Siberian permafrost dated around 10 million years. This species was named 'Bacillus massiliglaciei' strain Marseille-P2600 T (= CSUR P2600 = DSM 102861).